(untitled) ("Conference on Universal Science Research 2023", 2024)
This article explores the topic of verbs, focusing on the different types of verbs that exist in the English language. The abstract provides an overview of the various categories of verbs and their functions, highlighting the importance of understanding verb usage for effective communication.